Analisis Perencanaan Strategis Program Studi Pendidikan Guru Sekolah Dasar (PGSD) FKIP UNU Cirebon Menggunakan Metode SWOT - Endang Sri Budi Herawati; Adiman Adiman; Rusi Rusmiati Aliyyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research aims to: (1) To know the position of quadrant of the PGSD FKIP UNU Cirebon study program using swot method, (2) to know short-term strategic alternatives that can be applied to PGSD FKIP UNU Cirebon based on SWOT Method. The research approach used is a qualitative case study model supported by quantitative data and descriptive explanations. Data collection technique using questionnaire that first performed validity test with expert judgement technique. Data analysis techniques using Miles and Hubberman models. The results showed that: (1) the PGSD study program was in the position of quadrant II with a strength value of 0.533 and a threat 0.314. (2) The strategy that needs to be done in the PGSD FKIP UNU Cirebon is to diversify the strategy. The research conclusions are: (1) the PGSD study program of UNU Cirebon is in a fairly stable condition of ornganization, but faces many obstacles (threats); (2) The diversification strategy that must be carried out is to include academic quality, implementation of The Tri Dharma of Higher Education, and human resources. Keyword: Strategic Planning, SWOT Method, Higher Education